Determinants of real stock return of pharmaceutical products and materials companies - Marzban , Hojjatollah; Sotudeh, Reza; Piri , Habib (Social Determinants of Health, 2023)
Background: The present study aimed to investigate the factors that determine the actual efficiency of pharmaceutical companies. Methods: This study was an applied and descriptive-correlation research. Using the financial information of 28 pharmaceutical materials and products companies of Tehran Stock Exchange during 2013-2016, modeling of multiple variables on the real returns of pharmaceutical companies was performed. Data entered to excel and were calculated and the relationship between independent and dependent variables was analyzed by performing multiple regression tests in Eviews software. Results: There is a significance association between company size and real stock returns, but there was no relationship between assets and real stock returns and between equity returns and real stock returns. Between financial leverage and real stock returns, between price-to-earnings ratio and real stock returns; a significance association was observed between the ratio of book value to the market and the real stock return, and between the margin profit and the real stock return. Conclusion: Considering the importance of the factors determining the real return of pharmaceutical products and materials companies, it is expected that the financial characteristics of pharmaceutical companies and Stock returns on the Tehran Stock Exchange should be used by planners as a guide for investors in Tehran Stock Exchange.